2018
DOI: 10.14744/phd.2018.06978
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Factors Affecting the Sleep Quality of Psychiatry Patients Through Structural Equation Model

Abstract: Psikiyatri hastalarının uyku kalitesini etkileyen faktörlerin yapısal eşitlik modeli ile incelenmesi U yku, içsel ve dışsal uyaranlar ile tekrar bilinçli döneme dönülebilen bilinçsizlik dönemini kapsayan fizyolojik bir süreçtir. Uyku iki ana dönemden oluşmaktadır. REM (Rapid Eye Movement) uykusu olarak adlandırılan aktif uyku döneminde, vücut gevşer, hızlı göz hareketleri ve hızlı beyin dalgaları gözlenir. Kişi uykuya ilk daldığında REM uykusuyla başlar. NON-REM döneminde ise yavaş göz hareketleri görülür. Uyk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
4
1
1
Order By: Relevance
“…In the current study, more than half of the patients (57.4%) with 95%CI: [52%-62%] were reported poor sleep quality which is in agreement with different previous studies which had reported high prevalence of poor sleep quality [27][28][29] . The current finding was higher than the other studies done before probably because of different study settings and study years, duration of the illness, tools used to assess sleep quality and inclusion criteria of the study participants [30][31][32] .…”
Section: Discussioncontrasting
confidence: 70%
“…In the current study, more than half of the patients (57.4%) with 95%CI: [52%-62%] were reported poor sleep quality which is in agreement with different previous studies which had reported high prevalence of poor sleep quality [27][28][29] . The current finding was higher than the other studies done before probably because of different study settings and study years, duration of the illness, tools used to assess sleep quality and inclusion criteria of the study participants [30][31][32] .…”
Section: Discussioncontrasting
confidence: 70%
“…Sleep quality is the feeling of being refreshed, energized, and ready for a new day after waking up. Sleep is one of the most important concepts that determine people's quality of life and ensure the smooth functioning of their daily routines 27 . Nocturia, which is one of the symptoms of BPH and is defined as urinating two or more times during the night, causes insomnia and negatively affects the patient's sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is one of the most important concepts that determine people's quality of life and ensure the smooth functioning of their daily routines. 27 Nocturia, which is one of the symptoms of BPH and is defined as urinating two or more times during the night, causes insomnia and negatively affects the patient's sleep quality. Our study findings indicate that patients experience a decrease in sleep quality due to an increase in urination frequency, sudden urgency to urinate, and interrupted sleep due to nocturia.…”
Section: Theme 2 Social Disconnectionmentioning
confidence: 99%
“…Örsal et al 16 defined sleep quality as ‘the efficiency of sleep’. It consists of several components: subjective sleep quality, delay to onset, duration, habitual sleep activity, primary sleep disorder, daytime dysfunction and use of opiates or sedatives.…”
Section: Introductionmentioning
confidence: 99%